2018
DOI: 10.1107/s2053229618012706
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, crystal structure and cytotoxic activity of novel 5-methyl-4-thiopyrimidine derivatives

Abstract: This article presents the synthesis of three new 4-thiopyrimidine derivatives obtained from ethyl 4-methyl-2-phenyl-6-sulfanylpyrimidine-5-carboxylate as the starting material, namely, ethyl 4-[(4-chlorobenzyl)sulfanyl]-6-methyl-2phenylpyrimidine-5-carboxylate, C 21 H 19 ClN 2 O 2 S, (2), {4-[(4-chlorobenzyl)sulfanyl]-6-methyl-2-phenylpyrimidin-5-yl}methanol, C 19 H 17 ClN 2 OS, (3), and 4-[(4-chlorobenzyl)sulfanyl]-5,6-dimethyl-2-phenylpyrimidine, C 19 H 17 ClN 2 S, (4), which vary in the substituent at the 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
(24 reference statements)
1
8
0
Order By: Relevance
“…Generally, pyrimidines possessing a 4-benzylsulfanyl group (3a and 3b) exhibit stronger toxicity than their amino analogues (3c-3j). Considering our previous observation [14], it appears that the substitution in the phenyl ring of the benzyl group, with both electron-withdrawing (4-Cl) and electron-donating groups (2-CH 3 , 3b), enhances their toxic properties. Compound 3b decreased the cell viability in low concentration and, for this reason, was excluded from further biological investigations.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Generally, pyrimidines possessing a 4-benzylsulfanyl group (3a and 3b) exhibit stronger toxicity than their amino analogues (3c-3j). Considering our previous observation [14], it appears that the substitution in the phenyl ring of the benzyl group, with both electron-withdrawing (4-Cl) and electron-donating groups (2-CH 3 , 3b), enhances their toxic properties. Compound 3b decreased the cell viability in low concentration and, for this reason, was excluded from further biological investigations.…”
Section: Discussionmentioning
confidence: 78%
“…Its MIC ranged from 4 to 32 mg/mL, depending on the strain [13]. Additionally, we observed that the hydroxylation of 4-[(4-chlorobenzyl)sulfanyl]-5,6-dimethyl-2phenylpyrimidine to its 5-hydroxymethyl derivative enhances the cytotoxicity significantly towards both normal (survival of normal human endothelial cells, 58% vs. 1%) and cancer cell lines (IC50 in the range > 100-55 µM vs. 17-38 µM, depending on the cancer cell line) [14].…”
Section: General Procedures For the Preparation Of 2a And 2bmentioning
confidence: 99%
See 1 more Smart Citation
“…FMOs can play a significant role during molecular interactions . The chemical reactivity and stability might be determined by the energy gap of FMO. The electronic properties of CPFH, CCPH, and BCPH were determined by FMOs at the CAM-B3LYP/6-311G (d,p) level. The FMOs consist of HOMO, LUMO, HOMO – 1, LUMO + 1, HOMO – 2, LUMO + 2, and their energy gaps (Δ E ) are presented in Table .…”
Section: Results and Discussion (Computational)mentioning
confidence: 99%
“…[47] The energy gap of FMO may influence photo-catalytic activity and stability. [48][49][50][51][52][53][54][55][56] The HOMO-LUMO energy difference has a low value, indicating strong reactivity, and poor mechanical strength. [57] If the HUMO LUMO energy break is large, the inverse is true.…”
Section: Frontier Molecular Orbital (Fmo) Analysismentioning
confidence: 99%